Self-Management Programs on eGFR, Depression, and Quality of Life among Patients with Chronic Kidney Disease: A Meta-Analysis - Mei-Chen Lee, RN, PhD; Shu-Fang Vivienne Wu, RN, PhD; Nan-Chen Hsieh, PhD; Juin-Ming Tsai, PhD (Elsevier, 2016)
Purpose: Chronic kidney disease (CKD) is a condition characterized by the gradual loss of kidney function over time. Self-management programs have been widely applied to chronic disease education programs, which are designed to delay deteriorating kidney functions, preclude depression, and improve quality of life. This study aims to analyze effectiveness of self-management programs in bettering CKD patients' eGFR, mitigating depression symptoms and improving quality of life in randomized control or clinical trials. Methods: Using key terms, a search was conducted in English-language, peer-reviewed journals on CKD that were published between 2002 and 2014 on databases including CINAHL, Cochrane Library, MEDLINE. The measurable variables included CKD patients' eGFR, depression, and quality of life. Random and fixed effects meta analysis were applied with standard error and correlation based measure of effect size. Results: Eight studies met the inclusion criteria. A self-management program significantly impacted CKD patients' depression and mental quality-of-life dimensions, with an effect size of .29 [95% confidence interval (CI) (0.07, 0.53)] and −.42 [95% CI (−0.75, −0.10)]. However, the intervention of a self-management program had no significant effect on patients' eGFR as well as physical quality-of-life dimensions, with effect sizes of .06 [95% CI (−0.69, 0.81)] and −.16 [95% CI (−0.81, 0.50)]. Conclusions: Self-management programs of patients with chronic kidney disease can improve the depression and mental quality of life. Aside from providing more objective evidence-based results, this study provides a reference for clinical health care personnel who tend to patients with CKD.